STUDI PEROMBAKAN ZAT WARNA TEKSTIL REMAZOL RED RB SECARA AEROB MENGGUNAKAN BAKTERI ENTEROBACTER AEROGENES YANG DIISOLASI DARI LUMPUR LIMBAH TEKSTIL - Sastrawidana, I Dewa (Jurnal Kimia (Journal of Chemistry), 2012)
The objective of this research is to study the potential use microorganism which is identified as Enterobacter aerogenes isolated from sludge of textile wastewater treatment plant. Reactor was operated to treat remazol red RB azo dyes under aerobic condition. The performance of the bioreactor was evaluated by monitoring color removal within various pH of the medium, dye concentrations and incubation times. The degradation products were characterized by UV–vis techniques. The result showed, Enterobacter aerogenes bacteria was able to successfully decolourize 75 mg/L of remazol red RB azo dyes under aerobic condition, at pH 7-8 and for seven days incubation with biodegradation efficiency of up to 87,9%.
Keywords: Enterobacter aerogenes, remazol red RB, sludge textile wastewater